Gastrointestinal stromal tumour as a rare association with neurofibromatosis type 1. Issue 2 (21st February 2018) - Hurley, Rhona H; McCormick, Michael; Elhassan, Mohamad; Nicholson, Gary
Abstract: Gastrointestinal stromal tumours (GIST) are rare tumours of mesenchymal origin. These can be associated with neurofibromatosis type 1 (NF1), which is an autosomal dominant disorder. The prevalence of GIST in NF1 is estimated at 3.9–25%. This paper describes the presentation of a GIST arising from the jejenum in a 75-year-old lady with NF1, who presented with gastrointestinal bleeding. This was diagnosed by CT angiography. She was managed with laparotomy, with resection of small bowel, and an ischaemic segment of large bowel with two primary anastomoses. Pathology showed GIST of spindle cell type (Figs 3 and 4 ), 90 mm in size, with complete local excision. The patient was discharged on the eighth post-operative day and is currently undergoing regular clinic follow-up after multidisciplinary team meeting discussion.